Digital Media for Teachers in Vocational Schools: Digital Competence of 21st Century Educators - Setuju, Setuju; Widowati , Asri; Ratnawati , Dianna; Wijayanti, Astuti (Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Digital competency is a challenge and necessity for educators in the 21st century, especially in vocational schools. This study aims to bridge the gap by comprehensive review of digital media as a component of digital competency for teachers in Vocational Education and Training (VET). Data were collected from the Scopus, Research Gate, and Scholar databases based on inclusion and exclusion criteria. This study employs content analysis on 11 articles published in international journals indexed by Scopus between 2018 and 2024. The stages carried out include formulating material based on research questions, selecting relevant journal articles, analyzing main topics, interpreting data, identifying categories to develop digital skills, reporting findings, drawing conclusions, and suggesting further research. The findings show several technologies to develop educators' digital competence, such as blogs, websites, mobile smartphones, video conferencing, digital content and new digital devices. Project-based learning as an alternative instructional model for developing digital competencies using digital media. Digital media influences digital competence and its domain. Future studies could carry out empirical investigations based on this finding to further enhance digital competence among VET teachers.